PERBEDAAN HASIL RIAS WAJAH KOREKTIF PADA WAJAH BULAT MENGGUNAKAN TEKNIK VERTIKAL DAN HORIZONTAL APLIKASI BLUSH ON GRADASI - Ulhaq, Nailah Dhiya; Sri Usodoningtyas; Octaverina Kecvara Pritasari; Sri Dwiyanti (Program Studi Pendidikan Tata Rias, 2025)
The ideal face shape is oval, one of the non-ideal face shapes is a round face shape. In doing corrective makeup on a round face, the gradation blush application technique is done so that the face looks ideal. The purpose of this study was to determine the difference between vertical and horizontal techniques of gradation blush application and to determine the level of respondents' preference for makeup results. This type of research is experimental research. The samples in this study were 5 women who had round faces and applied gradation blush. The independent variable in this study is the application of blush vertical technique and horizontal technique (X), and the dependent variable is the level of influence of gradation blush application technique (Y). Observations were conducted by 30 expert respondents in the field of Cosmetology and Beauty Science who provided value and liking data using an observation sheet as a research instrument. Data analysis techniques using Independent T-Test and average value. The results of the T Test are known Sig. (2-tailed) of 0.001 (0.001 <0.05), it is concluded that there is a significant difference in the makeup results on round faces to achieve ideal facial makeup using vertical and horizontal techniques of gradation blush application. The respondent's level of liking for the final result of corrective makeup on a round face using the vertical technique of gradation blush application obtained an average value of 3.68 which means that the respondent really likes it than the final result of corrective makeup using horizontal technique. Keywords: Blush On Gradation, Corrective Makeup, Round Face.